Post-marketing safety evaluation of the intravenous anti-influenza neuraminidase inhibitor peramivir: A drug-use investigation in patients with high risk factors. Issue 10 (October 2016) - Komeda, Takuji; Ishii, Shingo; Itoh, Yumiko; Sanekata, Masaki; Yoshikawa, Takayoshi; Shimada, Jingoro
Abstract: Peramivir, the only injectable anti-influenza neuraminidase inhibitor medically available in Japan at present, is considered first-line treatment in patients with high risk factors for influenza exacerbation. We conducted a drug-use investigation of peramivir in inpatients with high risk factors (old age, pregnancy, and underlying disease such as chronic respiratory disease) from January 2010 to March 2013. Data of 772 patients from 124 facilities across Japan were collected; peramivir's safety in 770 patients and effectiveness in 688 patients were examined. In total, 412 adverse events were observed in 219 patients (28.4%). Of these, 155 events were adverse drug reactions (ADRs) observed in 98 patients (12.7%). Major ADRs (≥2%) were increased aspartate aminotransferase (5.1%), increased alanine aminotransferase (3.8%) and decreased white blood cell count (2.5%). Fourteen serious ADRs were observed in 12 patients (1.6%). All serious ADRs were resolved or improved except for two events for which outcomes were unknown. Multivariate analyses revealed that ADR incidences were significantly associated with these four backgrounds of patients: medical history, no influenza vaccination, renal impairment and other infection(s). With regard to its effectiveness, the median time to alleviation of both influenza symptoms and fever was 3 days, including the first day of administration, which was the same as in other previous surveillance studies. This surveillance study indicated the safety of peramivir in the treatment of influenza inpatients with high risk factors under routine clinical settings.